Human Rights Violation in the Manifestation of Indonesia's Inefficacious Covid-19 Policies Towards the Lower Socio-Economic Class - Dellvin Sergio (International Journal of Business, Economics, and Social Development, 2022)
Indonesia’s surging number of Covid-19 positive cases may be happening due to its own manifestation through implementing ineffective laws which then led to the resurgence of the policy crisis. Indonesia is deemed to have failed in handling the overwhelming pandemic. The imbalance of emergency fund allocation between the recovery of the economy and health sector also conveys Indonesia’s top priority. Policies made by the state also prove its failure in accommodating vulnerable people especially those who live in poverty. The application of the top-down policy affects those with financial insecurity then also burdened by extraordinary crimes such as corruption of social assistance mid pandemic. To implement an adequate policy which can respect, protect, fulfill, it is important to address poverty affected by covid policies through the lens of human rights, whether it is violated or fulfilled. The use of recent studies, official data, laws, policies, and human rights approaches will help indicate how people living in poverty are still marginalized of their rights to adequate standards of living pre and midst pandemic. Moving forward, those who live in poverty must live free from discrimination and stereotypes such as lazy, unlucky, undeserving, etc. which contributes to the exclusion and exploitation of this vulnerable group. This research will seek poverty as a human rights issue, it will show how this vulnerable group has been the victim of injustice and demand accountability. Through proper analysis, these findings will also set out appropriate and applicable solutions for the well-being of this group mid and post pandemic.